The impact of nutrition on visual cognitive performance in the nutrition, vision, and cognition in sport study - Beathard, Karen M.; Georghiades, Nicos; Goulart, Jenna B.; Riviere, Aaron J.; Sullivan, Caroline; Mascarro, Melanie; Riechman, Steven E. (Frontiers in Nutrition, 2023)
The purpose of this study was to examine the influence of nutritional intake on visual perceptual-cognitive performance (VCP) in young healthy adults. Ninety-eight healthy men (n=38) and women (n=60) aged 18 to 33 years participated and maintained their usual dietary intake throughout the study. VCP was measured using the NeuroTracker™ CORE (NT) 3-Dimensional (3-D) software program (15 training sessions) over a 15-day period. Food logs and extensive lifestyle measures including body composition, cardiovascular health, sleep and exercise patterns, and general readiness to perform were collected. Mean intake from ten food logs collected over the 15 days were analyzed using Nutribase software. Statistical analyses were performed in SPSS using repeated measures ANOVA including significant covariates when appropriate. Males consumed significantly more calories, macronutrients, cholesterol, choline, and zinc and performed significantly better on VCP than the females. Participants who consumed more than 40% of kcals from carbohydrates (P=0.038), less than 24% of kcals from protein (P=0.009), more than 2,000 μg/day lutein/zeaxanthin or more than 1.8 mg/day vitamin B2 performed significantly better on VCP than those who consumed less than those amounts, respectively. VCP is an important dimension of cognitive function and in the present study is influenced by higher carbohydrate, lutein/zeaxanthin, and vitamin B2 dietary intake while high protein consumption and the female sex negatively impacted VCP.